AES encryption of resource allocation for ultra-reliable and enhanced mobile broadband IoT applications in fog network - Ahmed Alqourabah, Eissa Abdulsalam (2022)
The cloud computing paradigm has evolved toward the edge in recent years in order to give improved Quality of Service (QoS) to Internet of Things (IoT) devices. However, because fog network technology's resource capacity is limited, it's critical to efficiently connect IoT applications with demanding QoS requirements to the available network infrastructure. We design a joint user association and resource allocation problem in the fog network's downlink in aforementioned research, taking into account the ever-increasing demand for QoS standards imposed by UltraReliable Low Latency Communications (URLLC) and Enhanced Mobile BroadBand (EMBB) services. First, we enforce the analytical framework using an Analytic Hierarchy Process (AHP) to assess the priority of different QoS requirements of heterogeneous IoT applications at the fog network. We then create a two-sided matching game using the AHP to establish a solid connection between the fog network architecture and IoT devices. We next encrypt the data using the Advanced Encryption Standard (AES) technique to safeguard it against theft and misuse